Materiality and social practice: transformative capacities of intercultural encounters - Maran, Joseph; Stockhammer, Philipp (Oxbow Books, 2012)
Materiality and Social Practice investigates the transformative potential arising from the interplay between material forms, social practices and intercultural relations. Such a focus necessitates an approach that takes a transcultural perspective as a fundamental methodology and, then a broader understanding of the inter-relationship between humans and objects. Adopting a transcultural approach forces us to change archaeology's approach towards items coming from the outside. By using them mostly for reconstructing systems of exchange or for chronology, archaeology has for a long time reduced
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Konferenzschrift; Sachkultur; Kulturkontakt; Bronzezeit; Mittelmeerraum